Polymorphism of detoxification genes and predisposition to the development of Parkinson's disease in Uzbek individuals - Khalimova, Khanifa; Raimova, Malika; Matmurodov, Rustam; Rasulova, Khurshidakhon; Burnasheva, Amina; Jmirko, Yekaterina; Mukhamedov, Rustam (European Medical, Health and Pharmaceutical Journal, 2011)
According to our research, Uzbek individuals with Parkinson's disease have high prevalence of 0/0 polymorphisms of GSTT1 and GSTM1 genes, as well as combinations of GSTT1 (0/0)/GSTM1/(0/0) genotypes. These mutations are associated with an earlier debut of the disease, its mixed form, and rapid rate of progression. Determination of mutations in GSTT1 and GSTM1 genes of xenobiotic detoxification in patients with Parkinson's disease confirms multifactorial nature of this pathology and the role of the influence of various external factors in the modification of clinical signs of disease and its prognosis.
Keywords: mutace; dospělí; Genetic Testing; Statistics as Topic; Female; Parkinsonova nemoc; statistika jako téma; Adult; ženské pohlaví; lidé; výběr pacientů; Patient Selection; Mutation; genetická predispozice k nemoci; Aged, 80 and over; Genetic Predisposition to Disease; Male; Aged; polymorfismus genetický; genetické testování; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Polymorphism, Genetic; Middle Aged; Parkinson Disease; Humans